STRUKTUR KOMUNITAS NEKTON DI DANAU SIOMBAK KECAMATAN MEDAN MARELAN KOTA MEDAN Community Structure of Nekton in Siombak Lake Subdistrict of Medan Marelan, Medan City. - Adil Junaidi; Mohammad Basyuni; Ahmad Muhtadi (AQUACOASTMARINE, 2015)
Siombak Lake is an artificial lake formed as a result of sand dredging activity formerly. This Lake is influenced by the tides. This study aims to determine the structure of nekton community. This study was carried out from May to July 2014. Data collection were nekton species composition and abundance, as well as water quality data as a supporter. Data were analyzed with a diversity index, uniformity index, dominance index. The results showed there were 7 of the Ordo, of which 6 ordo belongs to fish and 1 ordo of shrimp. Slinding (Ambassis uroatenia) was found to be caught at most in the amount of 237 and 64% relative abundance. Diversity nekton in Siombak Lake was medium (the range of 1 to 3) that was 1.07. Generallly dominance index 0.5, showing no species dominating. Similarity index was 0.48 indicating individual spreading differently.Keywords: Diversity, Dominance, Evenness, Lake Siombak, Nekton.